2016
DOI: 10.18632/oncotarget.13656
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ZNF609 functions as a competitive endogenous RNA to regulate AKT3 expression by sponging miR-150-5p in Hirschsprung's disease

Abstract: Research over the past decade suggested critical roles for circular RNAs in the natural growth and disease progression. However, it remains poorly defined whether the circular RNAs participate in Hirschsprung disease (HSCR). Here, we reported that the cir-ZNF609 was down-regulated in HSCR compared with normal bowel tissues. Furthermore, suppression of cir-ZNF609 inhibited the proliferation and migration of cells. We screened out several putative cir-ZNF609 ceRNAs of which the AKT3 transcript was selected. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 36 publications
1
109
1
2
Order By: Relevance
“…Although the circRNAs have been widely studied in human (Chen et al, 2016; Peng et al, 2016), systematic studies of plant circRNAs are just beginning. The development and senescence of leaves are very complex processes, which involve thousands of genes and multiple layers of regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the circRNAs have been widely studied in human (Chen et al, 2016; Peng et al, 2016), systematic studies of plant circRNAs are just beginning. The development and senescence of leaves are very complex processes, which involve thousands of genes and multiple layers of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies revealed that circRNAs can regulate gene expression at the transcriptional and posttranscriptional levels (Ashwal-Fluss et al, 2014; Li et al, 2015; Wang, 2015). Furthermore, circRNAs could serve as miRNA sponges by sequestering and preventing microRNAs from binding corresponding target genes (Hansen et al, 2013; Liu Q. et al, 2016; Peng et al, 2016). Nevertheless, the biogenesis and function of circRNAs remains to be studied (Chen and Shan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…circRNA-ZNF609 functions as a ceRNA to regulate AKT3 expression by sponging miR-150-5p in Hirschsprung's disease. 8 As a new form of post-transcriptional control, this network has a great potential implication in disease research. In addition, growing evidence suggests that circRNAs are highly enriched in mammalian brain tissues and are often derived from the genes specific for neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, circ‐ZNF609 is necessary for skeletal myoblast proliferation and can be translated into a protein in a splicing‐dependent and cap‐independent manner, providing an example of a protein‐coding circRNA in eukaryotes . circZNF609 is also expressed in neurons as well as in bowel tissues, where it is down‐regulated in Hirschsprung disease …”
Section: Circrna In Cardiovascular Diseasesmentioning
confidence: 99%